A Case of Simultaneous Surgical Correction of Tetralogy of Fallot Combined with Tracheal Stenosis in a One-Year-Old Child - Hanna V. Maistriuk; Yevhen O. Rudenko; Iaroslav P. Truba; Ivan V. Dziuryi; Oleksandr V. Metlenko; Zoia O. Synelnykova (Ukrainian Journal of Cardiovascular Surgery, 2025)
Congenital tracheal stenosis formed by complete cartilage rings is a rare disorder, occurring in 1:64,500 newborns. Concomitant heart defects significantly complicate the course of the disease and its surgical management. The natural course of complete cartilage ring tracheal stenosis carries a mortality of up to 80 %. Currently, simultaneous surgical intervention with the use of cardiopulmonary bypass in cases of concomitant congenital heart defects is the “gold standard” of treatment and is associated with satisfactory outcomes.Aim. To present and analyze a case of simultaneous surgical correction of congenital long-segment complete cartilage ring tracheal stenosis and tetralogy of Fallot.Clinical case. We present a clinical case of successful single-stage correction of tetralogy of Fallot with tracheal reconstruction using the slide tracheoplasty technique in a child aged 1 year and 5 months. The diagnosis of tetralogy of Fallot was made prenatally, and congenital tracheal stenosis was identified due to the inability to perform endotracheal intubation during routine surgery for congenital heart disease. The patient was referred to a thoracic surgeon for consultation. Tracheobronchoscopy and computed tomography revealed long-segment complete cartilage ring stenosis, and a decision was made to perform simultaneous correction of the congenital defects. The patient underwent successful simultaneous correction of tetralogy of Fallot and slide tracheoplasty under cardiopulmonary bypass with bronchoscopic guidance. The total duration of the surgery was 420 minutes. The patient was extubated as planned 96 hours after control tracheobronchoscopy. There were no complications during the intraoperative or postoperative periods. The patient remained in the intensive care unit for 6 days and in the hospital for 17 days. Tracheobronchoscopy five months after surgery revealed no restenosis or granulation tissue.Conclusions. Simultaneous surgical correction and a thorough multidisciplinary approach in the treatment of congenital long-segment complete cartilage ring tracheal stenosis with tetralogy of Fallot demonstrate satisfactory postoperative outcomes. Slide tracheoplasty is currently the gold standard in the surgical treatment of long-segment complete cartilage ring tracheal stenosis.